Semaphorin5A expression in the developing chick telencephalon. - Pineda Tenor, Daniel; Garcia Diaz, Beatriz; Olmos, José Luis; Dávila-Cansino, José Carlos; Real-Avilés, María Ángeles; Guirado-Hidalgo, Salvador (Elsevier, 2005)
In the present study, we analyzed the expression of Semaphorin5A (Sema5A), a gene implicated in axon guidance and many other processes of neuronal development, in the developing chick telencephalon. By using a heterologous mouse probe and in situ hybridization techniques, we showed distinct patterns of Sema5A expression within the chick telencephalon. In early development, Sema5A was present in pallial regions, mainly in the neuroepithelium and in the deep mantle of ventral and lateral pallia, and in the subpallium. As development proceeds, some ventral pallial derivatives maintained a moderate to strong Sema5A expression, whereas other lateral or dorsal pallial derivatives showed low to moderate expression of Sema5A. The overall expression of Sema5A during development in the chick telencephalon was similar to that reported in mouse. Moreover, the expression of Sema5A in mesencephalic, diencephalic, and telencephalic centers related to the tectofugal system suggests an important role of this gene in the development.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/12480
Keywords: Telencéfalo - Modelos animales; Neurobiología; Gene expression pattern; Olfactory system; Visual system; In situ hybridization; Birds